Ownership and Control over Publicly Accessible Platform Data - Scassa, Teresa (Université d'Ottawa | University of Ottawa, 2019)
Purpose: This paper examines how claims to ‘ownership’ are asserted over publicly accessible platform data and critically assesses the nature and scope of rights to reuse these data. Approach: Using Airbnb as a case study, this paper examines the data ecosystem that arises around publicly accessible platform data. It analyses current statute and case law in order to understand the state of the law around the scraping of such data. Practical Implications: The nature of some sharing economy platforms requires that a large subset of their data be publicly accessible. These data can be used to understand how platform companies operate, to assess their compliance with laws and regulations, and to evaluate their social and economic impacts. They can also be used in different kinds of data analytics. Such data are therefore sought after by civil society organizations, researchers, entrepreneurs, and regulators. This paper considers who has a right to control access to and use of this data, and builds an argument for a consideration of the public interest in data scraping. Findings: This paper demonstrates that there is considerable uncertainty about the practice of data scraping, and that there are risks in allowing the law to evolve in the context of battles between business competitors without a consideration of the broader public interest in data scraping. It argues for a data ecosystem approach that can keep the public dimension issues more squarely within the frame when data scraping is judicially considered.
Keywords: information law; information technology law; data scraping; copyright law; intellectual property law